Capital Taxation and Investment: Matching 100 Years of Wealth Inequality Dynamics - Gregor Boehl; Thomas Fischer (Lund University, School of Economics and Management, Department of Economics, 2017)
Using a parsimonious, analytically tractable dynamic model, we are able to explain up to 100 years of the available data on the dynamics of top-wealth shares for several countries. We build a micro-founded model of heterogeneous agents in which - in addition to stochastic returns on investment - individuals disagree marginally on their expectations of future returns and thus hold different asset positions. We show that, given a positive tax on capital gains, the distribution converges to a double Pareto distribution for which the degree of wealth inequality decreases with the tax rate. Closed-form solutions confirm that without government intervention there is infinite inequality. Moreover, transition dynamics are shown to increase with the tax rate. We discuss the model's ability to match the measured wealth inequality for the US, the UK, Sweden, and France, both in levels and transitions. The heterogeneous development in the different countries and across time can be traced back to different tax regimes.
Keywords: C63; D31; G11; H23; 330; Wealth inequality; capital taxation; stochastic simulation; heterogeneity